A visible high efficiency and polarization-insensitive 34-level dielectric metasurface hologram. Issue 42 (17th May 2017) - Xiaofang Su,; Li, Guanhai; Yang, Hui; Zhao, Zengyue; Yu, Feilong; Chen, Xiaoshuang; Lu, Wei
Abstract : A polarization-insensitive dielectric metasurface of 34 phase level is proposed to reproduce a holographic image in the visible region. Abstract : We propose a dielectric metasurface of 34 phase level, to reproduce the holographic image in the visible region. With normal incident circular polarized illumination, imaging efficiency as high as 59.72% is achieved at 560 nm wavelength. Consisting of non-resonant meta-cells, the proposed polarization-insensitive dielectric metasurface performs well in a broad band from 480 nm to 660 nm. Numerical results also indicate that the metasurface hologram maintains high fidelity within a wide-angle incidence (0–25°), and show high tolerance to fabrication errors. The high efficiency, broadband, wide-angle, and high fabrication tolerance metasurface based on the hologram, can be used in the fields of display, security, data storage, and information processing.